Optimized LMS: A Solution to Online Learning in Covid-19 (International Journal of Innovative Research in Computer Science & Technology, 2020)
Over the world, school and universities have  been closed for a considerable length of time. Instruction  has ended up being principle worry in the midst of  coronavirus emergency in the nation. At some point in the  second seven day stretch of March, state governments the  nation over started closing down schools and universities  incidentally as a measure to contain the spread of novel  coronavirus. It’s near a month and there is no conviction  when they will revive. This is significant time for the  instruction division. As the days pass by with no quick  answer for stop the episode of covid-19, school and college  terminations won’t just have a transient effect on the  coherence of learning for in excess of 285 million youthful  students in India yet in addition incite sweeping monetary  and cultural outcomes. Due to quick mechanical  advancements over the previous decade, online-learning is  as a rule generally utilized and productivity to fill the hole  made by suspended class learning.
Keywords: E- Learning; LMS; Adaptive E- Learning